KARA UMOWNA - KOMPENSACJA CZY REPRESJA? - Skowrońska-Bocian, Elżbieta (Zeszyty Prawnicze, 2017)
Contractual Indemnity - Compensation or Reprisal? Summary A contractual indemnity has been regulated in article 483 and 484 of the Civil Code. Parties may decide that a damage resulting from non-performance or improper performance of a non-pecuniary obligation shall be redressed in such a way that a debtor shall pay a creditor a specified amount, even if its extent differs from an extent of a damage incurred by a creditor. There is a discrepancy between the doctrine and judicial decisions as to the possibility of claiming a contractual indemnity by a creditor who did not incur a damage as a result of non-performance or improper performance of an obligation. Those in favour of an opinion according to which a creditor may claim a contractual indemnity even if he did not incur a damage stress its repressive character. The supporters of a notion that a damage on the side of a creditor constitutes a prerequisite for a claim to pay a contractual indemnity invoke the substance of the article 483 § 1 of the Civil Code. Pursuant to the provision the aim of a contractual indemnity is to redress a damage resulting from non-performance or improper performance of an obligation. The author of this study takes a position that a creditor is entitled to a contractual indemnity only if he sustained a damage as a result of non-performance or improper performance of an obligation. It is indicated in the substance of articles 483 § 1 and 484 § 1 of the Civil Code. Such an interpretation neither impairs a protection of an interest of a creditor nor excludes the repressive function of a contractual indemnity. The other interpretation, shaped many years ago, is no longer up-to-date due to socio-economic and legal changes effected in Poland after 1989. Notwithstanding, within the confines of a binding principle of liberty of contract (article 3 5 3 1 of the Civil Code), a contractual clause is admissible, according to which a debtor obligates himself to pay a specified amount in the event of non-performance or improper performance of an obligation, also if a creditor does not sustain any damage. However, such a clause does not constitute a contractual indemnity in the light of the article 483 § 1 of the Civil Code. It is a clause of a guarantee character. A contractual provision is also admissible, according to which a creditor, in the event of non-performance or improper performance of an obligation, may claim from debtor an amount specified in an agreement, beside an indemnity on general principles.